2019
DOI: 10.1001/jama.2019.18254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rocuronium vs Succinylcholine on Endotracheal Intubation Success Rate Among Patients Undergoing Out-of-Hospital Rapid Sequence Intubation

Abstract: IMPORTANCE Rocuronium and succinylcholine are often used for rapid sequence intubation, although the comparative efficacy of these paralytic agents for achieving successful intubation in an emergency setting has not been evaluated in clinical trials. Succinylcholine use has been associated with several adverse events not reported with rocuronium.OBJECTIVE To assess the noninferiority of rocuronium vs succinylcholine for tracheal intubation in out-of-hospital emergency situations. DESIGN, SETTING AND PARTICIPAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 45 publications
(74 reference statements)
3
54
2
2
Order By: Relevance
“…In our study we demonstrated a first-pass success rate of 79% with DL and 95% with VL, which is comparable to the existing literature for DL but better for VL in the prehospital setting [ 10 , 11 ]. The first pass success rate for in-hospital emergency ETI ranges from 75% to 85% with DL [ 15 , 18 , 19 ], and up to 96% with VL [ 16 , 20 , 21 ]. Mackie and colleagues could demonstrate that first pass success could be significantly increased from 59.2 to 85.1% with the C-MAC video-laryngoscope in 163 emergency intubations by emergency registrars [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study we demonstrated a first-pass success rate of 79% with DL and 95% with VL, which is comparable to the existing literature for DL but better for VL in the prehospital setting [ 10 , 11 ]. The first pass success rate for in-hospital emergency ETI ranges from 75% to 85% with DL [ 15 , 18 , 19 ], and up to 96% with VL [ 16 , 20 , 21 ]. Mackie and colleagues could demonstrate that first pass success could be significantly increased from 59.2 to 85.1% with the C-MAC video-laryngoscope in 163 emergency intubations by emergency registrars [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study there was no difference between well-experienced physicians with more than 100 ETIs and less-experienced physicians. Referring to Mackie and colleagues LEP probably were able to intubate with high success rates with VL [ 22 ] and the success rates with DL are comparable to other physician-based preclinical ETI rates with DL [ 19 ]. Because of the study design with focus on comparison of VL and DL, preplanned patient number in both groups for this particular question would be too small to answer it with high statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…Tracheal intubation is a crucial intervention in emergency settings [ 1 ], and sedation in emergency procedures greatly improves its ease and safety [ 2 ]. Therefore, in patients who require emergency tracheal intubation, rapid sequence intubation is the recommended airway management technique [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of rocuronium into clinical practice the use of the priming principle has almost disappeared [1]. Large doses of rocuronium are usually recommended when tracheal intubation must be achieved rapidly [1]. However, there are several reports that a priming dose of rocuronium administered 2-4 mins before an intubating dose accelerates neuromuscular blockade by 30-60 s. Consequently, tracheal intubation conditions are created within 90 s of an intubating dose of rocuronium [2,3].…”
Section: Introductionmentioning
confidence: 99%